An Analysis of Children’s Concerns in Migration Legal Instruments in Ghana - Agoe, P.A. (University of Ghana, 2012)
Migration has become a phenomenon that affects the lives of many people today. Children are affected as well in diverse ways by migration. Most countries lack comprehensive policies on migration which can harness its gains for mutual benefits and reduce its negative impacts. Meanwhile, migration has become a major process in many populations, including Ghana’s. Children have also been participating in migration in various ways; as independent migrants, as moving along with migrating parents or other adults and as left behind by their migrant parents. It is against the background that migration laws and other instruments do not often have perspectives of children considered that the present study examined how existing laws in Ghana related to migration have concerns, if any of children. Ghana was the first country to have ratified the Convention on the Rights of the Child (CRC), yet there are serious situations that threaten their rights and wellbeing such as the negative effects of migration that are probably not addressed with policies or legal instruments. Other situations of migration also make them vulnerable to separation from families, exploitation and abuse. Meanwhile, the Millennium Summit of the UN held in 2000 adopted eight goals popularly known as the Millennium Development Goals (MDGs); and most target children. The present study examined the following laws (legal instruments), The Immigration Act, 2000 (Act 573), The Citizenship Act, 2000 (Act 591), The Refugee Law, 1992 (PNDCL 305D) and The Human Trafficking Act, 2005 (Act 694), and the finding show that it is The Human Trafficking Act, 2005 that explicitly mentions children and their concerns. The study argues that it is important that migration laws and policies have concerns of children considered. Children should be specifically mentioned in them and their needs adequately provided.
Thesis (MA)
Keywords: Migration; Children; Phenomenon; Convention